A possible origin of dayside Pc1 magnetic pulsations observed at high latitudes - Safargaleev, V.; Serebryanskaya, A.; Koustov, A.; Lester, M.; Pchelkina, E.; Vasilyev, A. (CCSD, 2004)
International audience Induction magnetometer observations of dayside Pc1 activity at Barentsburg (BAB, Spitsbergen archipelago, 78.05°N, 14.12°E) are combined with data from two magnetometers located in Scandinavia and the Kola peninsula. Seven events with very large negative IMF B z components were considered. For all of the events, the cusp location was expected to be significantly shifted equatorward from the statistical position such that the BAB magnetometer was located well inside the polar cap. The DMSP particle data indicated that the BAB magnetometer was indeed inside the polar cap, whereas other magnetometers were collocated with the ionospheric projections of the cusp, the low-latitude boundary layer or the boundary plasma sheet. Pc1 magnetic pulsations were observed only at BAB. In three cases, for which SuperDARN convection data were available, the Pc1 activity correlated with intervals of large-scale convection reconfiguration, such that the plasma flow crossing the BAB location was associated with newly-reconnected magnetic flux tubes drifting tailward. The convection reconfigurations were in response to a decrease in the IMF B y component. We argue that the source of the observed Pc1 pulsations is anisotropic plasma of the depletion layer within the magnetosheath. The plasma anisotropy supports the excitation of electromagnetic ion cyclotron waves that are detectable with a ground-based magnetometer when the flux tubes containing the unstable plasma become connected to the Earth's ionosphere in the course of the dayside reconnection processes.